Perception of cold and heat pattern identification in diseases: a survey of Korean medicine doctors - Kwang-Ho Bae; Youngseop Lee; Ki-Hyun Park; Youngheum Yoon; Sujeong Mun; Siwoo Lee (Integrative Medicine Research)
Background: This study aimed to investigate the extent to which Korean Medicine doctors consider cold and heat pattern identification when prescribing herbal treatment for a disease. Methods: A survey was sent by e-mail to 15,841 members of the Association of Korean Medicine for whom member information was registered. Of these, 699 (4.4%) members participated in the survey. The survey included questions regarding the frequency of use of cold and heat pattern identification in deciding a herbal treatment prescription, the diseases for which cold and heat pattern identification-related herbal treatment was most efficacious, the type of herbal treatment prescribed, and the duration of the treatment. Results: Of the 699 respondents, 591 (84.5%) reported that they considered cold and heat when prescribing herbal treatment. The diseases for which consideration of cold and heat patterns was effective were, in order, menopausal disorder (124, 18.3%), chronic rhinitis (98, 14.5%), dyspepsia (94, 13.9%), hwa-byung (92, 13.6%), diarrhea (83, 12.3%), dysmenorrhea (61, 9.0%), headache (59, 8.7%), inflammation in the digestive tract (58, 8.6%), coldness in hands and feet (58, 8.6%), and atopic dermatitis (55, 8.1%). The typical treatment duration differed widely for different diseases: atopic dermatitis was most frequently treated for >2 months (38, 34.5%), whereas diarrhea was most frequently treated for ≤ 10 days (73, 43.6%). Conclusion: These findings indicate that cold and heat pattern identification is a useful tool employed by Korean Medicine doctors. This study may provide a basis for clinical research investigating the effect of pattern identification-based treatment of diseases.